Engaging with C. H. Dodd on the Gospel of John: Sixty Years of Tradition and Interpretation. Edited by Tom Thatcher and Catrin H. Williams - Edwards, Ruth B. (The journal of theological studies, 2014)
C. H. Dodd’s two major works on John, The Interpretation of the Fourth Gospel (1953) and Historical Tradition in the Fourth Gospel (1963), are rightly considered landmarks in the history of Johanninne scholarship. In this beautifully produced book fifteen scholars from Europe, the USA, and Australia reflect on Dodd's work in the light of more recent scholarship. This is no volume of adulatory ‘hero-worship’, but a genuine attempt to assess both the strengths and weaknesses of Dodd's scholarly contribution., The stimulating introduction (pp. 1–28) by Tom Thatcher, ‘The semeiotics of history’, is itself critical of Dodd for his lack of explicit methodology. Thatcher focuses on Dodd's view of the composition of John's Gospel, particularly his conviction that John drew on oral tradition.